Paradoks Digital: Pengaruh ChatGPT dan Keaktifan Akademik terhadap Produktivitas Publikasi Mahasiswa Pascasarjana PAI - Mahfudz Khudhori; Naomi Fahma; Benny Prasetya; Khoiriyah Khoiriyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2026)
The phenomenon of Artificial Intelligence (AI) usage, particularly Chat Generative Pre-trained Transformer (ChatGPT), among postgraduate students is increasingly massive, yet its impact on the quality and quantity of scientific publications remains an academic debate. This study aims to analyze the influence of ChatGPT utilization and academic engagement on the scientific publication productivity of Master of Islamic Education students at the Ahmad Dahlan Institute (IAD) Probolinggo. This research employed a quantitative method with an associative approach. Data were collected from 66 respondents selected via simple random sampling technique and analyzed using multiple linear regression. The results reveal a digital paradox where ChatGPT utilization has a significant but negative effect on publication productivity (Sig. 0.017; coefficient -0.423), indicating that unfiltered technological dependency reduces research originality. Conversely, academic engagement has a significant positive effect (Sig. 0.001; coefficient 0.649), serving as the primary determinant of academic success. Simultaneously, both variables contribute 17.8% to productivity. This study concludes that high AI adoption must be balanced with academic integrity and muraqabah (self-surveillance) principles to avoid cognitive laziness. This study recommends the necessity of ethical regulations for AI usage in higher education to maintain scientific work quality.5